2021
DOI: 10.1186/s40643-021-00380-8
|View full text |Cite
|
Sign up to set email alerts
|

l-Lactic acid production from fructose by chitosan film-coated sodium alginate-polyvinyl alcohol immobilized Lactobacillus pentosus cells and its kinetic analysis

Abstract: Under the optimal conditions of immobilization and fermentation, the highest LA yield of 0.966 ± 0.006 g/g fructose and production rate of 2.426 ± 0.018 g/(L × h) with an error of -0.5% and -0.2% to the predicted results were obtained from batch fermentation by the CS film-coated SA-PVA immobilized L. pentosus cells. The LA yield and production rate of these immobilized cells were 2.7% and 10.1% higher than that of normal SA-PVA immobilized cells respectively, and they were 5.7% and 48.4% higher than that of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…found that repeated batch fermentation using Lacticaseibacillus casei in alginate entrapped cells decreased the fermentation time by half with volumetric productivity of 0.625 g/l h compared to 0.375 g/l h using free cells fermentation; therefore, immobilized cells could be used in repetitive batch fermentation for more than 40 days, where the maximum productivity in the present study was 1.03 g/l h. In the same direction, fermentation of glucose using L. casei in immobilized form on gluten pellets needs shorter time (18 h) to produce higher LA (42 g/l) compared to free cells [44]. Also, immobilized cells of Lactiplantibacillus pentosus had higher heat stability and higher LA production rate from fructose [45]. Moreover, Lactiplantibacillus plantarum could use industrial wastes such as whey as substrates for LA production [46].…”
Section: Discussionmentioning
confidence: 63%
“…found that repeated batch fermentation using Lacticaseibacillus casei in alginate entrapped cells decreased the fermentation time by half with volumetric productivity of 0.625 g/l h compared to 0.375 g/l h using free cells fermentation; therefore, immobilized cells could be used in repetitive batch fermentation for more than 40 days, where the maximum productivity in the present study was 1.03 g/l h. In the same direction, fermentation of glucose using L. casei in immobilized form on gluten pellets needs shorter time (18 h) to produce higher LA (42 g/l) compared to free cells [44]. Also, immobilized cells of Lactiplantibacillus pentosus had higher heat stability and higher LA production rate from fructose [45]. Moreover, Lactiplantibacillus plantarum could use industrial wastes such as whey as substrates for LA production [46].…”
Section: Discussionmentioning
confidence: 63%
“…such as antagonistic against pathogens [28], broad-spectrum gram-positive bacteriocin preparation [22], improving the resistance of prawn [29], reducing carcinogenic substances by secreting N-nitrosodimethylamine [30], particularly the LA generation by the fermentation of this kind of strains [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…LA/L was produced (just over 50% of what is obtained at 100 rpm). Kinetic parameters of this test show that high agitation speeds can negatively in uence the conversion of the substrate since the conditions of the system are not related to lactobacilli, having values of for the logistic and Gompertz models (0.2471, 0.2427 g/L) lower than those obtained at 100 rpm, which in addition to suggesting that the shear stress affects the fermentation process, also the type of microorganism or its source (pure or non-pure strain) in uences the biotransformation process as indicated by Wang et al, [45] who reported from 0.2842 to 0.1834 g/L for commercial strain immobilized microorganisms and of 3.1813 g/L for pure strains, except for generalized Gompertz model (0.4593) in which the highest correlation coe cient was obtained (0.9055) and values between 0.0892 and 0.1689 1/h for the evaluated models, while the latency time is greater than the rst test, being above six hours.…”
Section: Mathematical Modeling Of Growth Kineticsmentioning
confidence: 96%